TERRESTRIAL FILAMENTOUS FUNGI FROM GRUTA DO CATAO (SAO DESIDERIO, BAHIA, NORTHEASTERN BRAZIL) SHOW HIGH LEVELS OF CELLULOSE DEGRADATION - Pires de Paula, Caio Cesar; Montoya, Quimi Vidaurre [UNESP]; Rodrigues, Andre [UNESP]; Bichuette, Maria Elina; Regali Seleghim, Mirna Helena (Natl Speleological Soc, 2016)
Subterranean environments are oligotrophic. However, few studies have investigated the composition and function of their terrestrial mycobiota. This study examined the functional role of filamentous cave fungi in cellulose degradation. Soil samples and dry sediment were collected in the surface epigean environment and two sites in the entrance and twilight zones inside Gruta do Catao in the Sao Desiderio karst area, state of Bahia, Brazil. Fungi were cultured from the samples, and the total organic carbon, culturable microorganisms, and carbon and nitrogen microbial biomasses were estimated. All fungal strains were evaluated for cellulase production in carboxymethylcellulose synthetic medium, and the enzymatic indices were estimated. We observed a significant difference (p <= 0.05) in physical, chemical, and biological parameters between epigean soil and cave sediments by Tukey's test. We recovered a total of 20 isolates comprising the genera Aspergillus (50.0%), Penicillium (25.0%), Talaromyces (10.0%), Trichoderma (5.0%), Purpureocillium (5.0%) and Scopulariopsis (5.0%). The majority of the isolates (90%) showed cellulolytic activity, which is a higher percentage compared to that normally reported in the literature for sediments. Thus there is a high probability that the filamentous fungi act in nutrient cycling, thereby contributing to the quality and maintenance of the cave ecosystem. These results indicate that parameters such as total organic carbon, biomass, and relative humidity that tend to differ between caves and epigean environments, provide selective pressures for microorganisms that use alternative sources of energy and nutrients.